Impact of the Dual Career on the perceived employability and intrapreneurial potential of elite student-athletes - Alberto Vidal-Vilaplana; Cristian Gregori-Faus; Pablo Jiménez-Jiménez; María Huertas González-Serrano (Retos: Nuevas Tendencias en Educación Física, Deportes y Recreación, 2025)
Introduction: Dual Career, which integrates academic training with sports practice, is highlighted as a protective factor for elite student-athletes, aiding in their preparation for a successful transition to the labor market. This study explores the impact of the competencies and intrapreneurial skills developed through Dual Career on perceived employability, emphasizing the critical role of this unique approach.